Natural Disasters In The Last Years Of The Ottoman State - Taşkın, Ünal (Fırat University, 2018)
The extent to which geography and climate influence human life has always been the subject of debate. There are some settlements that have had to confront with the negativities of the geography they were founded in. Palu is also one of these settlements. Palu was affected by these events due to earthquakes in some periods due to its presence on fault lines, and sometimes having to deal with droughts and famines due to the effect of climate. As a result of some disasters in the Ottoman and Republican eras, it moved away from its first settlement. Palu was forced to change its sett-lement twice as a result of fire and earthquakes. In this study, an evaluation will be made on the natural disasters in the Palu district in the last years of the Ottoman Empire.

Coğrafya ve iklimin insan yaşantısını ne derece etkilediği hep tartışma konusu olmuştur. Birtakım yerleşmeler vardır ki, kuruldukları coğrafyanın olumsuzlukla-rıyla, muhtelif devirlerde yüzleşmek zorunda kalmışlardır. Palu da bu yerleşim yerlerinden biridir. Fay hatları üzerinde bulunmasından dolayı kimi devirlerde depremlerle, kimi zamanda iklimin etkisiyle kuraklık ve kıtlıklarla boğuşmak zorunda kalan Palu, bu hadiselerden oldukça etkilenmiştir. Osmanlı ve Cumhuriyet devirlerinde yaşanan kimi afetler neticesinde ilk yerleşim yerinden uzaklaşmıştır. Öyle ki Palu, yangın ve dep-remler neticesinde yerleşim yerini iki defa değiştirmek zorunda kalmıştır. Bu çalışmada Osmanlı Devleti’nin son yıllarında Palu ilçesinde yaşa-nan tabii afetler üzerine bir değerlendirme yapılacaktır.
OSMANLI DEVLETİ’NİN SON YILLARINDA PALU’DA TABİİ AFETLER (1858-1910)